Maternal Hospital Mortality in Cotonou: Incidence, Care-Associated Adverse Events and Causes - DANGBEMEY, D. Patrice; DANGBEMEY, Djima Patrice; BIGOT, CÉDRIC EGNONWA PARFAIT; OGOUDJOBI, OGOURINDÉ MATHIEU; HOUNKPATIN, BENJAMIN IGNACE B.; TONATO EPSE BAGNAN, JOSIANE ANGÉLINA ADJOUA (My University, 2023)
: Despite the many efforts made to combat preventable maternal deaths, these still remain high in Benin. It was therefore important to revisit the causes but especially the adverse events associated with care (EIS) in maternity. Objective: Determine the incidence, adverse events associated with care and causes of intra hospital maternal mortality in cotonou. Methods: This was a cross-sectional maternal mortality review study with retrospective data collection. It covered all cases of maternal death recorded between 2017 and 2021 in two (2) reference university maternities in Cotonou. Adverse events associated with care and the patient were analyzed using the maternal death audit grid validated for Benin. SPSS.26 software was used for data analysis. Results: The in-hospital maternal mortality ratio in Cotonou was 2028 maternal deaths per 100,000 live births in 2021. Only 7.2% (n = 36) of deaths were audited. The deceased mothers were 29.8 ± 7.4 years old, with no fixed monthly income in 82.7% (n = 420). Serious adverse events associated with care were: delay in decision to refer in 37% (n = 188), non-medical referral in 85.8% (n = 436) of cases, inadequate pre-referral treatment in 25.7% of cases. In receiving maternities, delay in diagnosis and inappropriate treatment at the receiving maternity were noted respectively in 22.9% and 28.6% of cases of maternal death. The direct causes of maternal death were dominated by serious obstetric hemorrhage in 43.9% (n = 223). As for the indirect causes, they were dominated by anemia excluding obstetric hemorrhages in 21.5% (n = 109). Conclusion: The in-hospital maternal mortality ratio was very high in Cotonou. The main cause was severe obstetric hemorrhage. There were several serious healthcare-associated adverse events whose correct management would significantly reduce the incidence of maternal deaths.
Keywords: Keywords; Maternal Mortality; Adverse Events; Care; Cotonou